DEVELOPING OF INSTRUMENTS ON BASIC COMPETENCIES TO KNOW AND USE LETTERS, NUMBERS AND ETHICS WITH QUIZIZZ - Nugraha, Agri Triya; Rohendi, Dedi; Purnawan, Purnawan (Universitas Pendidikan Indonesia, 2021)
At the beginning of 2020, the emergency of the corona virus which caused an uproar in various countries in the world. Indonesia was one of the countries affected by the Covid-19 pandemic virus. Corona virus disease 2019 (COVID-2019). This has an impact on the world of education, in the midst of the Covid-19 pandemic, the learning and assessment process must still be carried out. Remote assessment evaluation tools can use applications, there are many applications that can be selected by the teacher. One of them is the quizizz application, researchers chose the quizizz application because the quizizz feature can be fully felt for free, while other applications need to upgrade to the paid version to get more varied features and the quizizz apllication can be played in support of exam mode and can load many participants. The research aims at; (1) Producing basic competency instruments to recognizing and using letters, numbers and tags in technical drawings (2) Obtaining instrument eligibility data based on expert tests, and (3) Obtaining instrument validation data, including validity, reliability, differentation, and diffuclty index. The method used is the ADDIE model development method consisting of steps of analysis, design, develop, implement and evaluate. The research has produced a basic competency instrument of recognizing and using letters, numbers and etiquette in the subject of technical drawing of class X light vehicle engineering in the form of an objective test of multiple choice 5 options totaling 30 items. The average result of the validation of all expert tests was 81,5 % with the very valid category. The results of the instrumen testing on students showed that all items were valid, high realibility with difficulty index ; 27 % easy, 60 % moderate, 13 % difficult, and their distinguishing power ; 80 % is in the fair category and 20 % is in the good category.